2020
DOI: 10.1017/ice.2020.381
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic prescription during the COVID-19 pandemic: A biphasic pattern

Abstract: To the Editor-The COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a public health problem of historic dimensions. However, this pandemic is occurring in the setting of an antimicrobial resistance crisis that is increasing at an alarming pace worldwide. Of concern, countries with a particularly high incidence of COVID-19 also have significant rates of infection caused by multidrug-resistant bacteria. During the 2009 influenza pandemic, coinfection with bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
107
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 8 publications
9
107
2
4
Order By: Relevance
“…This fact could be explained by the presence of patients with severe disease, long hospital stays, and hospital-acquired infections. This phenomenon has been proposed by other authors in previous studies [23,28].…”
Section: Discussionsupporting
confidence: 83%
“…This fact could be explained by the presence of patients with severe disease, long hospital stays, and hospital-acquired infections. This phenomenon has been proposed by other authors in previous studies [23,28].…”
Section: Discussionsupporting
confidence: 83%
“…1 Another single-center study from Spain showed increased use of amoxicillin-clavulanate during the early phase of the pandemic, followed by later increased utilization of broad-spectrum antibiotics. 2 There are several potential explanations for the observed increases in antimicrobial use including concerns of bacterial co-infection in suspected or newly diagnosed COVID-19 patients, increased risk of nosocomial infection due to administration of immunomodulatory therapy, reluctance to obtain diagnostic respiratory specimens, 3 diversion of clinical resources from stewardship activities during a time of crisis, and an increased proportion of hospitalizations being due to respiratory infections which typically prompt antibiotic therapy. Our finding that increases in antibiotic use were generalized across the VA and not restricted to facilities in areas with the highest case burden of COVID-19 suggests that issues not directly related to the care of COVID-19 patients contribute to the increased density of antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of increased antibiotic use during the COVID-19 pandemic have generally been from heavily impacted facilities or geographic regions and provide few details regarding patterns of antibiotic use. [1][2][3] To provide a broader overview of changes in antibiotic use in a healthcare system with a long-standing enterprise-wide commitment to antibiotic stewardship, we compared patterns of antibiotic use throughout the VA from January-May 2020 with corresponding time periods in prior years.…”
Section: Introductionmentioning
confidence: 99%
“…Abelenda-Alonso et al 6 showed an increase in amoxicillin/clavulanate and broad-spectrum antibiotic use within the pandemic period between 2019 and 2020. These data are similar to antimicrobial consumption data in our study, which suggests the same global behavior regarding their prescription.…”
Section: Discussionmentioning
confidence: 99%